Physico-chemical properties of pineapple peel extract and its application to isolate leucine from beef / Siti Roha Ab. Mutalib - Ab. Mutalib, Siti Roha (Institute of Graduate Studies, UiTM, 2015)
During canning and juice processing of pineapple, pineapple peel usually discharged. Discharged of pineapple peel during these productions will produce waste and lead to serious environmental pollution. In industrial practices, pineapple waste is either used as animal feed or disposed to the soil as waste. Pineapple peel contain valuable natural enzyme which is bromelain. Bromelain is enzyme which believed to have many benefits and very promising to the development of food and pharmaceutical industries. The purpose of this study is to isolate leucine from beef by using purified bromelain from pineapple peel extract. Purified bromelain powder from pineapple peel was produced through purification process. These include extraction from pineapple peel using purified water as a medium extraction, purification by cation exchange chromatography, desalting using continuous diafiltrator and followed by freeze drying. Each step was found to produce different effect on bromelain activity, protein content, specific enzyme activity and purification level…